The impact of COVID-19 on knowledge, attitude, and infection control behaviors among dentists - Hsin-Chung Cheng; Yan-Ju Chang; Shin-Ru Liao; Pallop Siewchaisakul; Sam Li-Sheng Chen (BMC, 2021)
Abstract Background This study seeks to elucidate the impact of COVID-19 on knowledge, attitude, and infection control behaviors among dentists. Methods Changes in knowledge, attitude, and infection control behaviors reported in 2020 (COVID-19 period) were compared to the historical control of the non-COVID-19 period in 2018. A proportional random sampling method was used to select the study samples from 400 dental institutions. The response rate was 69% in 2018 and 62.8% in 2020. A total of 276 dentists in 2018 and 251 dentists in 2020 responded to this questionnaire. Multiple logistic regression was used to assess the associations between factors and recommended infection control practices. Results High rates of correct COVID-19 knowledge (94.76%), fears of being infected with the virus (94%) and use of personal protective equipment (mask, glove and protection gown; 95%) were reported. We found that knowledge regarding environmental infection control, HIV transmission, and the window of HIV transmission were significantly higher in the post-COVID-19 period compared with the pre-COVID-19 period. High compliance rates of wearing mask, gloves and protection were reported. The number of dentists wearing a hair cap and a protective eye mask/face shield during the pandemic significantly increased compared with that noted before the COVID-19 pandemic. Factors associated with the use of a hair cap and an eye mask/face shield differed between the pre- and post-COVID-19 periods. The factors associated with compliance regarding environment infection control also differed between the pre- and post-COVID-19 periods. Conclusion The significant impact of COVID-19 on the knowledge, attitude, and infection control behaviors among dental care workers was observed in the current study. In particular, the use of hair caps and protective eye mask or face shields as well as environmental disinfection protocols has significantly improved. Trial registration TMU-JIRB: N201804006.